Are Teachers Objective and Impartial in Evaluating Business School Students or Do They Pursue Other Goals? - Senčar, Simon; Houdek, Petr, 1981-; Bahník, Štěpán; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The study aims to explore the extent of grade enhancement at a large Central European business school. We focus on characteristics of teachers that enhance grades, their motivations for this behavior and other factors in play. Employing qualitative interviews with academic staff, questionnaire (N = 68) and descriptive analysis of students’ grades (N = 993,639), we find ubiquitous enhancement of student assessment and grades. Nearly 70% of the questionnaire respondents admitted enhancing grades at least occasionally, supported by the finding of significant bunching of scores at grade thresholds. Oral examinations are the key source of grade enhancement as the method allows teachers to incorporate empathy and non-achievement factors in the assessment. We discovered a significant rounding bias – teachers’ tendency to round up numbers, explaining some part of grade enhancement. Therefore, a straightforward recommendation is to reduce oral examinations.
Vedoucí práce: Petr Houdek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses